Sold my soul for a student loan : higher education and the political economy of the future - Kirsch, Daniel (Daniel T.) (Praeger, 2019)
"With unprecedented student debt keeping an entire generation from realizing the "American Dream," this book sounds a warning about how that debt may undermine both higher education and our democracy"--